Adsorption of Methyl Orange Dyes on Oriented Co/Fe-MOF Bimetallic Organic Framework in Wastewater Treatment - Kim Ngan Thi Tran; Cao Phuong Khanh Phan; Vuong Thinh Ho; Hung Dung Chau; Thi Nhu Dung Nguyen (Universitas Gadjah Mada, 2023)
The production of highly efficient and reusable adsorbents that can be used in pigment treatment has been of great scientific interest. Metallic organic frameworks (MOFs) are considered a new type of material with extremely diverse structures and can be used as adsorbents to remove environmental pollutants. The selected Co/Fe-MOF material was synthesized in this study by using the solvent-thermal method. Then, the effects of several influencing factors such as adsorbent dosage, pH, initial concentration of MO, and exposure time on the adsorption capacity of methyl orange (MO) dyes by Co/Fe-MOF were evaluated. Under acidic conditions (pH 4), the effective removal of MO from aqueous solution reached equilibrium after 60 min upon exposure to MO at the concentration of 200 mg/L, and the adsorption capacity was 137.6 mg/g. The two models of adsorption isotherms, Freundlich and Langmuir, showed good compatibility with the experimental data, and the calculated correlation coefficients (R2) were both greater than 0.96. The MO adsorption efficiency was proposed to fit the pseudo-quadratic and pseudo-first-order kinetic models. Therefore, MOF materials can be considered as a potential agent for wastewater treatment, thereby providing a possible solution to solve water pollution.